HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN KONSTIPASI PADA LANSIA DI KOTA MADIUN - Amelia Dyah Kartika Sari; Bambang Wirjatmadi (Universitas Airlangga, 2016)
Elderly is the fi nal stage in human life which usually begins at age 60 years. Elderly phase characterized by decreased function of the body and more susceptible to diseases. One of the disease that are often experienced by the elderly is constipation. Constipation can be caused by various factors, one of which is lack of physical activity.The purpose ofthis study was to analyze the correlation between physical activity and constipation in Madiun City elderly. The subject, which collected using cluster random sampling and simple random sampling method, was 68 elderly which a week physical activity were scored using Physical Activity Scale for the Elderly questionnaire and constipation rate analyzedby Constipation Scoring System questionnaire. Statistic analysis was done using Spearman Correlation test. Results showed that the majority (73.5%) of respondents did not do enough physical activity, and as much as 66.2% of total respondents had constipation. There was a strong and positive correlation between physical activity and constipation in elderly (p = 0.000; r = 0.557) The conclusion of this study is that elderly in Madiun City who did enough physical activity tend to not have constipation.Keywords: physical activity, constipation, elderly